BUSANA KONTEMPORER BERGAYA PREPPY DENGAN PENERAPAN TEKNIK BONING - Azizah Al Hidayati; Fadri Rahmat; Desi Trisnawati; Desra Imelda (KAMPUS AKADEMIK PUBLISING, 2026)
Contemporary fashion represents a dynamic, liberated, and adaptive manifestation of modern clothing that evolves with time. It can be integrated into pre-existing styles to deliver a novel aesthetic, one of which is the preppy style—a dressing aesthetic inspired by elite preparatory school uniforms in the United States. This study re-explores contemporary preppy fashion, transforming its conventionally rigid nature into a more experimental and unique form through the application of the boning technique. The creation process is grounded in direct observation and a literature review, which encompass the visual analysis of relevant fashion brands implementing similar deconstructions, alongside a comprehensive review of academic journals concerning contemporary art evolution, preppy style characteristics, and boning technique applications. Based on this theoretical framework, silhouette exploration is executed utilizing the boning technique as the primary method to construct clean, rigid garment structures. To counterbalance this rigidity, garment details are enhanced through fabric manipulation techniques, including pleats, sequin embroidery, and fabric flower appliqués. The collection employs lurik woven textile as the primary wastra, combined with satin jacquard, cotton poplin, Madina cotton, and organza. This work is manifested into three apparel tiers: ready-to-wear, ready-to-wear deluxe, and haute couture. Designed specifically for high-presentation occasions such as fashion shows or galas, this collection is expected to contribute novel insights to aesthetic development and form exploration within contemporary fashion.